Rapid, on-site, and sensitive detection of aflatoxin M1 in milk products by using time-resolved fluorescence microsphere test strip. (March 2021) - Li, Miao; Wang, Haiming; Sun, Jiadi; Ji, Jian; Ye, Yongli; Lu, Xin; Zhang, Yinzhi; Sun, Xiulan
Abstract: Aflatoxin M1 (AFM1), a frequently occurring mycotoxin in milk and dairy products, causes acute and chronic poisoning. In this study, we developed a time-resolved fluorescence microsphere immunochromatographic test strip (TRFM–ICTS) combined with ultraviolet light for the rapid and quantitative detection of AFM1 in milk and its products. Polystyrene microspheres enclosing time-resolved fluorescent europium (III) [Eu(III)-TRFM] were prepared as a label and then conjugated to a monoclonal antibody. Pre-incubation was introduced for competitive recognition. Under optimal conditions, TRFM–ICTS had a linear range of 0.05–2.0 ng/mL with a 50% inhibitory concentration (IC50) of 0.204 ng/mL, which was nearly five–fold lower than those of ICTS in a traditional structure with traditional pretreatment (IC50 = 1.10 ng/mL). This test strip enhanced the sensitivity from 0.3 ng/mL (by using gold nanoparticles-strip method previously reported) to 0.019 ng/mL (by using this TRFM–ICTS method). The improved sensitivity may be due to the detection signals of immunoassay probes (with each fluorescence microsphere coupled with numbers of antibodies). TRFM–ICTS exhibited good recoveries ranging from 84.6% to 119.0% with a coefficient of variation (CV) lower than 8.31% in spiked samples, including milk powder, ultrahigh-temperature (UHT) and pasteurized milk. The results obtained using TRFM–ICTS were consistent with those obtained by ultrahigh–performance liquid chromatography–tandem mass spectrometry (UPLC–MS/MS) during testing of real milk samples. In addition, TRFM–ICTS has a longer storage period, which basically meets the needs of the commercial market. Owing to its high sensitivity and practicability, the proposed TRFM–ICTS can be used as a sensitive, simple, rapid, and versatile method for the quantitative detection of AFM1 in milk. Highlights: Developing a time-resolved fluorescent immunochromatographic assay for aflatoxin M1. Pre-incubation was introduced for competitive recognition. The sensitive and stable assay was used for AFM1 detection in milk. The assay could quantitatively detect AFM1 by consuming less monoclonal antibody. An immunostrip with a detection limit of 0.019 ng/mL for AFM1 was developed.